-first you have to consider the formula a perfect square: (aX+b)^2=(aX)^2+(2)(a)(b)+b^2
-You have to match the equation on the right with the problem.
-in the problem the number in from of x^2 is one and the number in form of X^2 in the formula is a. So a=1
-next look at the number in front of X in the problem: -20: and the number in front of X in the the formula is 2ab
so 2ab=-20 (a=1) so 2b=-20 and b=-10
-They problem has given you two of the three terms in the formula, but is missing is b^2. From above you know that b=-10 thus b^2=(-10)^2=100. what need to be added to the expression is 100.
Hope that helps. :)
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?